Special Issue on COVID19 - Editorial (Dr. Chinmay Pandya, 2020)
Dev Sanskriti Interdisciplinary International Journal (DSIIJ) is completing its 8 years of Journey. The journal is published by Dev Sanskriti University and is globally bringing quality conscious researches done on scientific and spiritual aspects of Dev Sanskriti (Divine Culture).  In the first half of year 2020, the whole globe has taken a back with the novel corona virus (COVID19) pandemic. It has affected every dimensions of human society and the whole world is collectively fighting the situation. During the time of crisis, this special issue of DSIIJ has attempted to contribute the awareness in the society through bringing researches on the indigenous techniques such as Yoga, Yagya, psychological tools along with focus on the new strategies in the field of journalism and tourism with ancient Indian wisdom for helping human civilization.  The need of time is immune boosting approaches and mental health care approaches. Serving the need, the vast literature of YugRishi Pandit Shriram Sharma Acharya on health is presented in the current issue, along with research articles on possible utility of Yoga for the same especially utilizing Hatha-yoga for reducing Kaph indicating symptoms during pandemic. Besides, the role of positive journalism and spiritual support for reviving the tourism sector is also covered in this issue along with technological approaches like Artificial intelligence by the world. Also, the pandemic has brought a big halt on the world economy, questioning its model's sustainability; hence, demanding a glimpse on the ancient Indian model of rural economy recommended by Mahatma Gandhi as a potential green-skill-based entrepreneurship solution for the globe, considering harmony with nature. With true pleasure, through the special issue of DSIIJ on COVID19, it is a small contribution of Dev Sanskriti University for the betterment of the world in the present crisis.